Zlepšení opakovatelnosti a reprodukovatelnosti testů podvozkových komponent - Konečný, Zdeněk (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
V rámci řešení diplomové práce „Zlepšení opakovatelnosti a reprodukovatelnosti testů podvozkových komponent“ je řešen problém měření radiální elasticity kulových kloubů s ohledem na opakovatelnost a reprodukovatelnost měření.

Within the Master´s Thesis „Repeatability and Reproducibility Improvement of Suspension Components Tests“ is resolution of a problem measurement of the radial elasticity of ball joint with regard for Repeatability and Reproducibility measurement.
Repeatability and Reproducibility Improvement of Suspension Components Tests
Keywords: Měření; kulový kloub; měřící zařízení; opakovatelnost; reprodukovatelnost; Measurement; Ball Joint; measuring equipment; Repeatability; Reproducibility